COLLEGE GYMNASIUMUNDER THE TEACHING BACKGROUND - Xu Haibo; Albattat, Ahmad; Jeong Chun Phuoc; Wang Baogui (International Journal of Multidisciplinary Research and Studies, 2022)
The operation and development of sports venues in colleges are in the early stage of reform. Since the sports venues in colleges not only have basic teaching functions but also have the functional characteristics of serving the public, how to achieve effective operation is the key to this research. By analyzing the actual situation of college gymnasiums at this stage, find out the dilemma of operation. The dilemma of the reform of the operation and management of sports venues in colleges and universities mainly exists in the management department and the sports venues. From the perspective of management departments, while reducing management functions, the level of supervision should be improved accordingly, and various policy standards of colleges and universities should be improved; In terms of sports venues, while ensuring basic functions, professional operations will be enhanced to improve operating income and public service levels.